Agos Water Solutions a business feasibility study - Jingco, Luelle Renee C.; Lim, Bruce Derrick S.; Lina, Theresa Candise P.; Santos, Christian Ernest N.
The use of alternative construction materials in the Philippines is a growing trend with more than twenty accredited technologies already in use. Though these technologies capitalize on the indigenous resources of the country, they are priced high and therefore cannot be used for mass residential housing for the poor. Kawayanihan is a Philippine company that supplies complete alternative building systems using bamboo and other indigenous materials. Its unique house design allows it to withstand both seismic loading and heavy wind drag caused by typhoons offering safety, stability and protection to those who will live in the structure. The house will be prefabricated at a production facility in Sta. Rosa, Laguna before being transported to its end users. The company also offers entire housing projects or community designs to help the government and non-government agencies alleviate the poverty situation in the country by decongesting urban areas. These communities will be equipped with bamboo harvesting facilities so that members of the community can exploit bamboo's other uses for income generation and can also use it as replacement materials should their houses need repairs. It is also important for the company to be able to train the homeowners with the proper maintenance of their houses so that the structural integrity of the house is never compromised. This will be achieved by providing on the job training for the home dwellers at the production facility so that while they are in the process of relocation they can also be provided with income in the form of monetary compensation for their labor at Kawayanihan's production facility. Through market segmentation, the city of Manila was identified as the area that has the greatest need for housing today. In fact, Manila has the highest population density of any major city in the world with 41,014 people/km2 and this can be seen by transients who pass through the city each day. The efforts of government organizations and non-government agencies to provide housing and shelter to the homeless and impoverished is insufficient to satisfy the demand for housing today as evidenced by the total housing need for 2010 in NCR of 83,500 houses. Therefore it is Kawayanihan's objective to mass produce low-cost housing and supply it to different agencies so that they will be able to fulfill their objectives more efficiently. The Sales and Marketing Department of the company will be in charge of obtaining customers to sustain Kawayanihan's operations from year to year. The strategy has two components; an awareness campaign to spark interest from the youth and by direct selling. The awareness campaign will rely heavily on online promotions, focusing on the Filipino youth aged 15-19 so that as early as that they can already develop an appreciation towards alternative building technologies. Direct selling is the primary tool that will be used by the company to expand its distribution channels. A financial analysis of Kawayanihan's first eight years of operations was conducted to determine the financial feasibility of the project. Financing will be obtained from the Center of Community Transformation (CCT) and from equities obtained after being registered by the SEC. Kawayanihan will turn a profit on its second year of operations. After performing marketing, technical as well as financial analysis of Kawayanihan, it can be concluded that the project is feasible from all three aspects and is one worth pursuing to help alleviate the poverty situation in the Philippines.